Cost of responding to the 2017 University of Washington Mumps Outbreak: A Prospective Analysis - Pike, Jamison (J Public Health Manag Pract, 2019)
OBJECTIVES: To estimate costs of labor and materials by the University of Washington (UW) and state and local public health departments (PHD) to respond to the February–June 2017 UW mumps outbreak, where 42 cases were identified among students (primarily sorority and fraternity members), staff, and associated community members DESIGN: We applied standard cost analysis methodology using a combined public health and university perspective to examine the cost of responding to the outbreak. SETTING: UW’s Seattle campus encompasses 703 acres with ≈32,000 undergraduate students. Nearly 15% of the undergraduate population are members of fraternities or sororities. Housing for the fraternities and sororities is adjacent to the UW campus and consists of 50 houses. PARTICIPANTS: During the outbreak, customized costing tools based on relevant staff or faculty positions and activities were provided to UW and Public Health—Seattle & King County, populated by each person participating in the outbreak response, then collected and analyzed. Laboratory hours and material costs were collected from Washington Department of Health and Minnesota Department of Health. MAIN OUTCOME MEASURE: Labor and material costs provided by UW and PHD during the outbreak were collected and categorized by payer and activity. RESULTS: Total costs to UW and PHD in responding to the outbreak were $282,762 ($6,692 per case). Of these, UW spent $160,064, while PHD spent $122,098. Labor accounted for 77% of total outbreak costs and UW response planning and coordination accounted for the largest amount of labor costs ($75,493) overall. CONCLUSIONS: Given the current university and public health department budget constraints, the response to the outbreak amounted to a significant use of resources. Labor was the largest driver of costs for the outbreak response; UW labor costs--related to campus response planning and coordination--dominated the total economic burden from public health and university perspectives.